1980
DOI: 10.1007/bf02408541
|View full text |Cite
|
Sign up to set email alerts
|

Decreased breaking strength of diabetic rat bone and its improvement by insulin treatment

Abstract: A simple instrument is described which measures the breaking strength of rat bones. The apparatus yields reproducible results and is suitable for use in measuring the strength of bones from both large and small animals. Diabetic rat femurs were more fragile and required less force to break in contrast to those from diabetic rats treated with insulin or normal rats. Daily insulin treatment significantly improved the bone cortical thickness and enhanced their capacity to withstand pressure, although these did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 11 publications
2
22
0
2
Order By: Relevance
“…The work of Dixit and Ekstrom on the biomechanical behavior of bone showed a decrease in the breaking strength of the femoral shaft of diabetic rats. 30 The relationship between osteopenia and Type 1 diabetes has now been well established, 31 while the effects of Type 2 diabetes on bone metabolism are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Dixit and Ekstrom on the biomechanical behavior of bone showed a decrease in the breaking strength of the femoral shaft of diabetic rats. 30 The relationship between osteopenia and Type 1 diabetes has now been well established, 31 while the effects of Type 2 diabetes on bone metabolism are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The breaking strength of the femur has been shown to be lower after 8 weeks of diabetes or more in STZ diabetic and diabetic BB rats (Dixit and Ekstrom 1980;Verhaeghe et al 1994), but not after 4 weeks (Funk et al 2000). Decreased torsional strength in rats that have been diabetic for 1 year persisted after correcting for smaller bone size (Einhorn et al 1988).…”
Section: Introductionmentioning
confidence: 95%
“…These authors also found that the bones from diabetic animals exhibited reduced strength-related properties, along with a compensatory increase in stiffness, suggesting a possible alteration in bone crystal structure. Bone strength has also been shown to be diminished in T1DM rats at the femur and the femoral neck (16,48). In a number of T1DM animal studies, histomorphometric analyses have shown that, irrespective of the model used, insulindeficient rats may exhibit reduced or absent bone formation and this decline is appreciated in relation to all bone surfaces examined, i.e., trabecular, periosteal, and endocortical (132)(133)(134).…”
Section: Effects Of Insulin On the Biomechanical And Microarchitecturmentioning
confidence: 99%